Case Report: Extensive Dermatitis Secondary to Severe Malnutrition, Zinc and Vitamin Deficiencies After Malabsorptive Bariatric Surgery - Herrera-Martínez, Aura D.; Junquera-Bañares, Sonia; Turrión-Merino, Lucía; Arrieta-Blanco, Francisco; Botella-Carretero, José; Vázquez-Martínez, Clotilde; Calañas-Continente, Alfonso (Frontiers in Endocrinology, 2021)
Bariatric surgery is one of the most effective treatments currently available for obesity and its derived comorbidities. However, complications may occur, especially when malabsorptive surgeries like a biliopancreatic diversion is performed. We present the case of a female patient whose obesity was treated with this technique, and in the 9th year of follow-up developed an extensive dermatitis secondary to zinc deficiency and malnutrition, precipitated by therapeutic non-compliance. A close surveillance of early symptoms and signs of nutritional deficiencies as well as chronic supplementation of vitamins and trace elements is required; this case illustrates the relevance of periodical, lifelong visits to a medical physician with special training and experience in the management of post bariatric surgery patients in order to prevent, diagnosis and early treat related complications.